PYROMETALLURGICAL PROCESS FOR ZINC ANALYSIS IN SPHALERITE APPLYING XRD AND XRF - Dahani, Wiwik; Kurniawati, Riskaviana; Sundari, Rita; Marwanza, Irfan; Rachman, Faisal (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2024)
This paper has analyzed dominant zinc element in sphalerite naturally found together with galena in mineral ore. Since pyrometallurgical route related to roasting process is very common to mineral dressing, therefore, this investigation has studied the effect of varied roasting time (30 min, 60 min, and 90 min) and temperature (500oC, 600oC, and 700oC) on zinc mineral examination using XRD (X-Ray Diffraction) and zinc element using XRF (X-Ray Fluorescence) analyses. Previous studies usually applied cheaper AAS (Atomic Absorption Spectrometer) for zinc analysis in aqueous solution, however, sphalerite is a solid matrix and therefore, this study has applied XRF to analyze zinc. Pyrometallurgical process of zinc mineral in sphalerite is related to mineral transformation in the form of ZnSO4, ZnS, and ZnO that cannot be detected by XRF. Therefore, this study has used XRD that can observe mineral transformation. The XRD pattern shows four intense peaks at 2θ (28o, 47o, 56o, and 76o) justified sphalerite (ZnS) sample with little amount of pyrite (FeS2) and galena (PbS) as impurities. The XRF analysis shows from 30 min to 90 min, the Zn content has increased remarkably at 700oC and Zn content looked stagnant at 500oC, while Zn content increased dramatically from 60 min to 90 min at 600oC. During roasting process at high temperature, ZnS mineral converted to ZnO and expelled SO2 gas due to oxidation reaction causing weight reduction. The study is valuable for mineral processing in searching for optimization.